Partial vs. complete course of antenatal corticosteroid prophylaxis: An Italian single center retrospective study - Xodo, Serena; Trombetta, Giulia; Celante, Lisa; Pittini, Carla; Driul, Lorenza; Cagnacci, Angelo; Londero, Ambrogio P. (Frontiers in Pediatrics, 2022)
Introduction. This study aimed to compare the outcomes of preterm infants given 12 mg versus 24 mg of betamethasone prophylaxis to understand whether a partial course of antenatal corticosteroids (CCS) could prevent or mitigate the major preterm birth complications. Methods. This is a retrospective single-center cohort study including neonates born between 24 and 34 weeks of gestation from 2001 to 2019 at the University Hospital of Udine. The study population was divided into two groups: one group received 12 mg, and another received a 24 mg dose of betamethasone before the delivery. A separate analysis was performed for single and multiple pregnancies. The two groups were evaluated for various neonatal outcomes. Results. The study population included a total of 1258 pregnancies and 1543 neonates delivered between 24 and 34 weeks of gestation, of which 1022 (803 single and 219 multiple pregnancies) were exposed to the complete CCS prophylaxis, whereas 236 (192 single and 44 multiple pregnancies) received the incomplete CCS prophylaxis. In single pregnancies, as for maternal characteristics, the most significant differences observed between the two groups are the following: a higher prevalence of spontaneous vaginal deliveries in the incomplete CCS prophylaxis (36.46% vs. 23.91%) and, by contrast, a higher prevalence of cesarean deliveries in the complete CCS prophylaxis group (75.72% vs. 63.02%). As for neonatal outcomes, the low Apgar score in the first and fifth minutes was significantly more prevalent in the incomplete CCS prophylaxis group compared with the complete CCS prophylaxis group. The group of incomplete CCS prophylaxis reported a higher occurrence of the following outcomes: IVH grade 3-4 (7.81% vs. 3.74%, p<0.05), PVL (7.29% vs. 1.99% p<0.05), ROP (23.96% vs. 18.06% p=0.062), and RDS (84.38% vs. 78.83% p=0.085). After adjusting for covariates, the complete CCS prophylaxis group in single pregnancies was significantly protective for IVH grade 3-4, PVL, and low Apgar’s scores. Similar results were found in multiple pregnancies except for RDS. Discussion. n conclusion, the evidence from this single-center retrospective study supports the preference for the complete CCS prophylaxis in women at risk of preterm birth because of its beneficial effect on the main adverse outcomes.